De Gaulle's 'Communauté'. A Bridge from Colonialism to Paternalism in Afrika - Willemot, Yves (Afrika Focus, 1988)
The importance of the French-African Communauté is more than just historical. Indeed, the present French-African relationship is not completely understandable without a knowledge of the Community, which was created by the constitution of the fifth French Republic (1958). President de Gaulle, who was its inspirator, realised that in the changing world the relation- ship between France and its colonial territories had to be adapted. The French-African Community was a federal structure in which the French-speaking territories south of the Sahara became autonomous republics. Yet their autonomy was substantially restricted: foreign affairs, defense, the economic and financial policy, justice, higher education, the policy concerning raw materials (e.g. uranium and oil), and the organisation of international transport and telecommunication were reserved for the federal institutions. Although four institutions were created within the Community (the Presidency, the Executive Board, the Senate and the Court of Arbitration), only the Presidency had real power: the ex- clusive legislative and executive competence in all Community matters. The function of Community President was reserved for the French President. Therefore it can undoubtedly be said that the French-African Community was not a genuine federal structure, but merely a constitutional arrangement which ensured France the exclusive control over its former African colonies. The African political leaders were also aware of this and claimed the abolition of the. French-African Community. Using the possibility for change, provided by the 78th article of the constitution, they demanded independence by the transfer of all reserved competences (1960). In order to avoid any rupture, France accepted on the condition that bilateral cooperation agreements would be signed simultaneously. These agreements, which were revised halfway the seventies and which are still in force today, provide France with an unique position in Africa. No former métropole has a comparable influence in Africa. Besides, the French-African Conference, which is organised anually since 1973, gives France an excellent forum to influence and control the policy of African states. At this Conference almost every former French colonie in Africa is present, some Belgian, British, Spanish and Portuguese territories participate as well. Moreover, the cooperation agreements explicitly allow France to maintain large troups in Africa and to give support by military intervention whenever it is necessary. France's strict control over one of the most important attributes of state sovereignity, namely defense, increases largely the already acuted dependency on Paris. Yet, the economic position of most of the former French colonies and territories in Africa is the best illustration of their present dependence. Still today more than 40% of their trade is realised with the former métropole (export: raw materials; import: finished goods). Moreover, most of them are members of the so-called "zone franc", a monetary zone which is completely controlled by the French authorities. The good relationship between France and Africa remained as a result of which extensive bilateral cooperation agreements could be signed within the framework of the French-African Community. This continuity has always been one of the main characteristics of the French policy in Africa. KEYWORDS:-Decolonisation -Francophone Africa-the French-African Community - French policy in Africa - 'La Communauté'